Dual-wavelength Q-switched thulium doped fiber laser with TiO2 film saturable absorber - Ahmad, Bilal A.; Rusdi, Muhammad Farid Mohd; Jusoh, Zulzilawati; Latiff, Anas Abdul; Harun, Sulaiman Wadi (National Institute of Optoelectronics, 2018)
We report a dual-wavelength Q-switched Thulium doped fiber laser based on a Titanium dioxide (TiO2) saturable absorber. The TiO2 was embedded in polyvinyl alcohol (PVA) film, which was then sandwiched in between two fiber ferrules in the cavity. By using a Thulium-doped fiber with a slightly larger core, it functions as intra-cavity spectral filter to allow dual-wavelength Q-switching regime to be achieved in the cavity. Our experimental results show that the fiber laser can simultaneously generate Q-switched microsecond pulses at 1954.43 nm and 1957.27 nm, which have the repetition rate varying from 12.89 kHz to 21.93 kHz and 0.54 µJ maximum pulse energy. Our proposed scheme is quite simple and thus it can be implemented at a low cost.